A complex interplay between H2A.Z and HP1 isoforms regulates pericentric heterochromatin - González, Jessica; Bosch-Presegué, Laia; Marazuela-Duque, Anna; Guitart-Solanes, Anna; Espinosa-Alcantud, María; Fernandez, Agustín F.; Brown, Jeremy P.; Ausió, Juan; Vazquez, Berta N.; Singh, Prim B.; Fraga, Mario F.; Vaquero, Alejandro (Frontiers in Cell and Developmental Biology, 2023)
Pericentric heterochromatin (PCH) plays an essential role in the maintenance of genome integrity and alterations in PCH have been linked to cancer and aging. HP1 α, β, and γ, are hallmarks of constitutive heterochromatin that are thought to promote PCH structure through binding to heterochromatin-specific histone modifications and interaction with a wide range of factors. Among the less understood components of PCH is the histone H2A variant H2A.Z, whose role in the organization and maintenance of PCH is poorly defined.Here we show that there is a complex interplay between H2A.Z and HP1 isoforms in PCH.While the loss of HP1α results in the accumulation of H2A.Z.1 in PCH, which is associated with a significant decrease in its mobile fraction, H2A.Z.1 binds preferentially to HP1β in these regions. Of note, H2A.Z.1 downregulation results in increased heterochromatinization and instability of PCH, reflected by accumulation of the major epigenetic hallmarks of heterochromatin in these regions and increased frequency of chromosome aberrations related to centromeric/pericentromeric defects. Our studies support a role for H2A.Z in genome stability and unveil a key role of H2A.Z in the regulation of heterochromatin-specific epigenetic modifications through a complex interplay with the HP1 isoforms.